General review of maximal aerobic velocity measurement at laboratory. Proposition of a new simplified protocol for maximal aerobic velocity assessment - Berthon, P.; Fellmann, N. (The Journal of Sports Medicine and Physical Fitness, 2002)
The maximal aerobic velocity concept developed since eighties is considered as either the minimal velocity which elicits the maximal aerobic consumption or as the "velocity associated to maximal oxygen consumption". Different methods for measuring maximal aerobic velocity on treadmill in laboratory conditions have been elaborated, but all these specific protocols measure Vamax either during a maximal oxygen consumption test or with an association of such a test. An inaccurate method presents a certain number of problems in the subsequent use of the results, for example in the elaboration of training programs, in the study of repeatability or in the determination of individual limit time. This study analyzes 14 different methods to understand their interests and limits in view to propose a general methodology for measuring Vamax. In brief, the test should be progressive and maximal without any rest period and of 17 to 20 min total duration. It should begin with a five min warm-up at 60-70% of the maximal aerobic power of the subjects. The beginning of the trial should be fixed so that four or five steps have to be run. The duration of the steps should be three min with a 1% slope and an increasing speed of 1.5 km x h-1 until complete exhaustion. The last steps could be reduced at two min for a 1 km h-1 increment. The maximal aerobic velocity is adjusted in relation to duration of the last step.